THE INFLUENCE OF SOCIAL MEDIA COMMUNICATION ON CONSUMER PERCEPTIONS OF BRANDS AND PURCHASE INTENTIONS IN THE PANDEMIC AND POST-PANDEMIC ERA: AN ANALYTICAL STUDY - Ricky Agusiady; Didin Saepudin; Zaenal Aripin (Organisasi Kreatif Indonesia Emas, 2024)
The global pandemic, particularly the COVID-19 pandemic, has resulted in fundamental changes in consumer behavior, triggering a transformation in their interactions with social media. This research explores the impact of social media communication on consumers' brand perceptions and purchase intentions amid the pandemic and post-pandemic era through a thorough literature review. Detailing findings from relevant journals and information sources, this research provides in-depth insights into the complex dynamics between social media, brand perception and consumer purchase decisions. The literature analysis includes an in-depth understanding of how social media influences the way consumers form perceptions of brands, modify their preferences, and ultimately affect purchase intentions. Findings from related studies are comprehensively integrated to produce a holistic view of the role of social media in shaping consumer behavior. The results of this literature review are expected to contribute to academic understanding and provide practical guidance for companies in adapting their marketing strategies to the evolving consumer dynamics in the pandemic and post-pandemic era.